Fault Exclusion in Multi-Constellation Global Navigation Satellite Systems. (26th June 2018) - Zhai, Yawei; Joerger, Mathieu; Pervan, Boris
Abstract : This paper comprehensively investigates the fault exclusion problem in multi-constellation Global Navigation Satellite Systems (GNSS). In future GNSS, the heightened likelihood of fault detection events will cause more interruptions in the continuity of the navigation operation. The main contribution of this paper is to establish the theoretical basis to quantify the contributions of fault events on continuity risk, therefore allowing us to assess the desired exclusion function performance based on specific continuity requirements. Accordingly, a new real-time exclusion algorithm is developed, for which the upper bounds on integrity risks are rigorously derived. Using the new method, performance is comprehensively investigated for two important civil aircraft navigation operations using various numbers of constellations. We show that high service availability can be achieved for both operations.